Going wire with insect - Mohd Tahir, Osman; Othman, Abdul Aziz; Mohd Yusof, Mohd Johari; Hussein, Mohd Kher (Universiti Putra Malaysia Press, 2013)
There is beauty to be found in everything including insects. Insect, a six-legged creature with three body parts, compound eyes and a pair of antennae could be found almost everywhere in our daily life. Some are beneficial and others could be considered as pest to many. One need not travel far to capture the experience with insect. By walking through our nearby gardens and parks we would increase our appreciation towards insects and could lead to greater interest in natural things and the environment. Hence this insect art project was introduced to further stimulate the appreciation of fauna in the environment especially the insects which have more than a million known species in the world. 3D wire insect were introduce to add another dimension of presenting enthralment and the exclusivity of this living object in the environment. When presented in the right way, the fascination of the insects amplifies with greater interest in and compassion for a greener tomorrow and greener human environment interaction.